THE EFFECT OF FREEZING ON THE PROCESSING OF DRIED REBON SHRIMP AS A FORM OF LOCAL FOOD DIVERSIFICATION - Rukmelia Rukmelia (Food ScienTech Journal, 2020)
Rebon shrimp is one of the seafood species of crustaceans which has a very small size compared to other types of crustaceans. But behind its small shape, rebon shrimp has tremendous benefits. Rebon shrimp is quite easy to find in the market and is in the cheap category compared to other shrimp prices. Rebon shrimp is a food ingredient that rots easily so that processing and preservation is needed to maintain its quality. One of them is freezing and drying. This method can extend shelf life and inhibit the growth of bacteria, molds and yeasts. It can increase the selling value of rebon shrimp. This is also done as an effort to support local Indonesian food. The purpose of this study was to obtain the best process in making dried rebon shrimp. In this study, two methods were carried out, namely: method A without freezing and method B with freezing. This research was conducted using a randomized block design with one factor of rebon shrimp with 2 treatments and 3 replications. The parameters tested were water content, rehydration time and organoleptic test. The results of analysis of various water content and rehydration time showed a very significant difference. From the research results, the highest water content was found in rebon shrimp with freezing is 5.4% and the lowest in rebon shrimp without freezing is 4.8%. The longest rehydration time for rebon shrimp with freezing is 2 minutes and the fastest rehydration time for rebon shrimp without freezing is 1 minute. The sensory test showed different results. For color and texture, the most preferred is dried rebon shrimp with freezing, while for aroma and appearance, the most preferred is dried shrimp with no freezing treatment.